The Effectiveness Study on the Application of Bai CiZhan to High School English Vocabulary Memory Strategy - Wu, Xiaodan (Forum for Linguistic Studies, 2025)
With the advancement of network technology and the increasing prevalence of smartphones, mobile-assisted vocabulary learning has gained flexibility and popularity among language learners. This study investigates the effectiveness of the Bai CiZhan learning application on English vocabulary acquisition and memory strategies among senior high school students. Using a quasi-experimental design with 100 participants (50 in the experimental group and 50 in the control group) over one semester, this research employed pre- and post-vocabulary tests and strategy questionnaires to evaluate the application's impact. Results demonstrated that students using Bai CiZhan achieved significantly higher vocabulary scores (M = 36.20, SD = 5.76) than the control group (M = 32.31, SD = 6.20; p < 0.001). Specifically, significant improvements were observed in English interpretation, synonym group analysis, and word spelling (all p < 0.01), whereas no significant difference was found in the selection of appropriate word forms. Strategy assessment revealed significant enhancements in spelling strategy, association strategy, and word formation strategy (all p < 0.05), with no significant improvements in repetition, contextual, flexible application, and metacognitive strategies. This study contributes to mobile-assisted language learning research by providing empirical evidence for the selective effectiveness of vocabulary learning applications in enhancing specific memory strategies. The findings suggest that while mobile applications offer innovative pathways for vocabulary acquisition, they should complement rather than replace traditional instruction in comprehensive vocabulary development for high school English learners.